Reevaluating claims of ecological speciation in Halichoeres bivittatus - Warren, Dan L.; Eytan, Ron I.; Dornburg, Alex; Iglesias, Teresa L.; Brandley, Matthew C.; Wainwright, Peter C. (Ecology and evolution, 2021)
Allopatry has traditionally been viewed as the primary driver of speciation in marine taxa, but the geography of the marine environment and the larval dispersal capabilities of many marine organisms render this view somewhat questionable. In marine fishes, one of the earliest and most highly cited empirical examples of ecological speciation with gene flow is the slippery dick wrasse, Halichoeres bivittatus. Evidence for this cryptic or incipient speciation event was primarily in the form of a deep divergence in a single mitochondrial locus between the northern and southern Gulf of Mexico, combined with a finding that these two haplotypes were associated with different habitat types (“tropical” vs. “subtropical”) in the Florida Keys and Bermuda, where they overlap. Here, we examine habitat assortment in the Florida Keys using a broader sampling of populations and habitat types than were available for the original study. We find no evidence to support the claim that haplotype frequencies differ between habitat types, and little evidence to support any differences between populations in the Keys. These results undermine claims of ecological speciation with gene flow in Halichoeres bivittatus. Future claims of this type should be supported by multiple lines of evidence that illuminate potential mechanisms and allow researchers to rule out alternative explanations for spatial patterns of genetic differences. In this study, we attempt to replicate one of the most highly cited cases of parapatric ecological speciation in marine fishes. Despite having larger sample sizes and a broader sampling of habitats than previous studies, we found no support for ecological speciation or speciation with gene flow.